From Pablo to Osama. Trafficking and Terrorist Networks, Government Bureaucracies, and Competitive Adaptation (Comentario Internacional: Revista del Centro Andino de Estudios Internacionales, 2010)
Reseña del libro de Michael Kenney, From Pablo to Osama. Trafficking and Terrorist Networks, Government Bureaucracies, and Competitive Adaptation, The Pennsylvania State University Press, United States, 2007